PENGARUH LITERASI AKUNTANSI DIGITAL DAN DIGITAL PAYMENT TERHADAP KINERJA KEUANGAN SALON DI SEMARANG BARAT - Windi Anggis Natussafaah; Munifah Munifah (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study used a quantitative approach with a survey method, distributing questionnaires to salon businesses in West Semarang. The number of respondents in this study was 100–150 businesses selected using a purposive sampling technique. The independent variables in this study were digital accounting literacy and digital payments, while the dependent variable was financial performance. The results showed that digital accounting literacy had a positive and significant effect on salon financial performance, as a good understanding of digital financial recording and reporting can improve the accuracy and transparency of financial information. Furthermore, the use of digital payments has also been shown to have a positive impact on financial performance, as it can speed up transactions, increase customer convenience, and facilitate automated recording. Simultaneously, these two variables contribute significantly to improving the financial performance of salon businesses.